2020
DOI: 10.3390/plants9070903
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydomonas reinhardtii, an Algal Model in the Nitrogen Cycle

Abstract: Nitrogen (N) is an essential constituent of all living organisms and the main limiting macronutrient. Even when dinitrogen gas is the most abundant form of N, it can only be used by fixing bacteria but is inaccessible to most organisms, algae among them. Algae preferentially use ammonium (NH4+) and nitrate (NO3−) for growth, and the reactions for their conversion into amino acids (N assimilation) constitute an important part of the nitrogen cycle by primary producers. Recently, it was claimed that algae are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 93 publications
(176 reference statements)
0
21
0
Order By: Relevance
“…MACC-360 were able to remove 100% of nitrate from TAP-M5 by the 3rd day. This nitrate removal can be explained by previous studies, which have shown nitrate assimilation reactions in Chlamydomonas reinhardtii ; it has been stated that nitrate is first reduced to nitrite in the cytoplasm by nitrate reductase, followed by its transfer to chloroplast, where it is further reduced to ammonia by nitrite reductase and this ammonia is then incorporated in carbon skeletons by the Glutamine Synthetase/Glutamine Oxoglutarate Aminotransferase (GS/GOGAT) cycle, which is responsible for the synthesis of glutamate [ 35 , 36 , 37 ]. For the nitrate reduction in the cytoplasm, first, nitrate needs to enter inside microalgae cells, a process which is carried out by nitrate transporters.…”
Section: Discussionmentioning
confidence: 99%
“…MACC-360 were able to remove 100% of nitrate from TAP-M5 by the 3rd day. This nitrate removal can be explained by previous studies, which have shown nitrate assimilation reactions in Chlamydomonas reinhardtii ; it has been stated that nitrate is first reduced to nitrite in the cytoplasm by nitrate reductase, followed by its transfer to chloroplast, where it is further reduced to ammonia by nitrite reductase and this ammonia is then incorporated in carbon skeletons by the Glutamine Synthetase/Glutamine Oxoglutarate Aminotransferase (GS/GOGAT) cycle, which is responsible for the synthesis of glutamate [ 35 , 36 , 37 ]. For the nitrate reduction in the cytoplasm, first, nitrate needs to enter inside microalgae cells, a process which is carried out by nitrate transporters.…”
Section: Discussionmentioning
confidence: 99%
“…This residual NO 2 − assimilation is enough to avoid NO 2 − dissimilation to N 2 O. In addition, NIT2 also controls other steps in NO 3 − assimilation, including NO 3 − /NO 2 − transporters [ 36 , 40 ] and NO metabolism-related proteins such as AOX1 [ 51 ], THB1 and THB2 [ 38 , 39 ], and probably CYP55, which increases in response to NO 3 − [ 29 ]. Moreover, a putative NO 3 − -dependent regulation of the N 2 O production, mediated by NIT2, is also supported by the significant increase in the N 2 O emission rate observed in M3 cells incubated in NO 3 − compared to those incubated in NO 2 − ( Figure 2 c).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two works have identified the flavodiiron proteins (FLVs) and cytochrome P450 (CYP55) as NO reductases (NORs) in Chlamydomonas [ 26 , 27 ]. The Cr FLVs belong to a singular family of O 2 and NO reductases that are ubiquitous in oxygenic photoautotrophs, including cyanobacteria, the rhizarian Paulinella chromatophora , green algae, mosses, lycophytes, and gymnosperms, but are absent in angiosperms [ 28 , 29 ]. The Chlamydomonas CYP55 is a cytochrome p450 NO reductase closely related to fungal p450 nor members, which are considered biomarkers for N 2 O production [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The living organisms present in nature have an enourmous versatility to metabolize most nitrogenous compounds. The paper by Bellido-Pedraza et al (2020) [ 1 ] reviews the N cycle in the model alga Chlamydomonas reinhardii [ 2 , 3 ] and its participation in different reactions of the N cycle [ 4 ]. The authors made particular emphasis of their description of new putative genes encoding enzymes involved in N-transforming reactions as NO and N 2 O production and their occurrence in other algae genomes.…”
mentioning
confidence: 99%